2018
DOI: 10.1016/j.icheatmasstransfer.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vortex generator shapes and pin fin perforations for enhancing water-based heat sink performance

Abstract: In this study, two models have been analysed numerically to examine the impact of the geometry and the working fluid under laminar flow on heat and flow characteristics. The first model is a perforated pinned heat sink (PPHS) and the second is a new design of a uniform micro-channel having different shapes of vortex generators (VGs) positioned at intervals along the base of the channel. The VG shapes are circular, triangular and rectangular, and are compared to each other based on constant volume. Models with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…On the other hand, the HC vortex generator has the lowest values of pressure drop as compared with the other enhanced models particularly at higher Reynolds numbers. This result is consistent with results of Al-Asadi et al (2018) research that showed the circular VG shape has lower pressure drop than symmetric triangular and square models.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, the HC vortex generator has the lowest values of pressure drop as compared with the other enhanced models particularly at higher Reynolds numbers. This result is consistent with results of Al-Asadi et al (2018) research that showed the circular VG shape has lower pressure drop than symmetric triangular and square models.…”
Section: Resultssupporting
confidence: 93%
“…The conjugate heat transfer model and validations against previous studies of the micro-channel is presented as in [1,5,6]. Al2O3 and SiO2 nanoparticles are considered to be separated from each other and well distributed in water as a base fluid at all ranges of concentrations to offer homogeneous nanofluid.…”
Section: Analysis and Modellingmentioning
confidence: 99%
“…This brings to fore the need to eliminate the generated heat as it could adversely affect the electronic chip. This can be achieved in a number of ways, using air and waterbase cooled heat sinks [1][2][3][4] and the use of mini-and micro-channel heat exchangers and/or advanced fluids [1,[5][6][7]. Micro-channel design is being modified rapidly to meet the recent improvement in electronic chips and to enhance the heat transfer rate [8].…”
Section: Introductionmentioning
confidence: 99%
“…Al-Asadi et al [18] explored a novel geometry of VGs to reinforce the 3D conjugate heat transfer of a laminar micro-channel flow by using a CFD technique. Al-Asadi et al [19] also reported another simulation to examine the impact of pin fin perforations under laminar heat transfer flow in heat sinks. Aravind and Deepu [20] enhanced the mass transfer in high-velocity fluid flows by combined lateral sweep VGs and dimple surfaces.…”
Section: Introductionmentioning
confidence: 99%